India: Politics and Threats to Academic Freedom - Altbach, Philip; Mathews, Eldho (International Higher Education, 2025)
<h3 id="higher-education-in-india-has-always-been-influenced-by-politics-but-the-current-bharatiya-janata-party-government-has-greatly-increased-politicization-political-interference-in-the-hiring-of-vice-chancellors-and-professors-restrictions-on-academic-freedom-and-other-problems-have-become-commonplace-this-interference-threatens-a-free-and-open-intellectual-environment-as-seen-in-recent-censorship-cases-and-punitive-actions-against-faculty-and-students-in-many-institutions" data-pm-slice="1 1 []">Higher education in India has always been influenced by politics, but the current Bharatiya Janata Party government has greatly increased politicization. Political interference in the hiring of vice-chancellors and professors, restrictions on academic freedom, and other problems have become commonplace. This interference threatens a free and open intellectual environment, as seen in recent censorship cases and punitive actions against faculty and students in many institutions.